AB0669 The risk factor of perinatal complication in the connective tissue disease patients. (23rd January 2014) - Shimada, H.; Dobashi, H.; Kanenishi, K.; Susaki, K.; Kameda, T.; Takeuchi, Y.; Izumikawa, M.; Nakashima, S.; Danjo, J.; Matsunaga, T.
Abstract : Background: Pregnancies and deliveries are the most important life events for women. Many of connective tissue disease (CTD) patients occur in childbearing age. Once, CTD patients tended to give up pregnancy because of the high risk for preterm birth and abortion.Recently, CTD patients in hope of pregnancy were increased because of advanced examinations and therapies for CTD. However, CTD patients more often complicate preterm birth and abortion, light for dates (LFD) in perinatal period in spite of advanced examinations and therapies. There is no clear answer whether these problems are associated with activity of underlying disease or dose of corticosteroid during pregnancy. Objectives: We reveal the relationship between perinatal complication and activity of underlying disease or dose of corticosteroid during pregnancy for pregnancy complicated with CTD (CTD-pregnancy) in our facility. Methods: We investigated retrospectively as follow; underlying disease, anti SS-A antibody, complication with antiphospholipid syndrome (APS), the mode of delivery, the rate of preterm birth and abortion, perinatal complication, dose of corticosteroid during pregnancy and neonatal birth weight. Results: Forty-three CTD-pregnancy patients were enrolled. Mean age was 30.5 years old, and mean CTD duration was 6.3 years on pregnancy. In this study, CTD-pregnancy patients had systemic lupus erythematosus (SLE), sjogren syndrome (SS), rheumatoid arthritis (RA), mixed connective tissue disease (MCTD), and so on. Six (17%) of all patients were exacerbated underlying disease during pregnancy. 3 cases of them needed corticosteroid pulse therapies because of their high disease activities. Positive anti SS-A antibody was found 16 cases (50%). However, there was no cardiac anomaly and arrythmia caused by anti SS-A antibody. Positive antiphospholipid antibody (aCL) revealed 14 cases (44%), and one of them had a preterm birth associated with APS. The rate of abortion was 9.3%, and the rate of preterm birth was 11.4%. The reason of abortion and preterm birth was high activity of underlying disease in all cases. There was no relationship between preterm birth, abortion, LFD or perinatal complication and dose of corticosteroid during pregnancy. Conclusions: In CTD-pregnancy, preterm birth and abortion, LFD, perinatal complication is associated with the activity of underlying disease. We did not establish the relationship between dose of corticosteroid and these problems in our study. Therefore, it is important for safer pregnancy and delivery to treat underlying disease strictly with corticosteroid. Disclosure of Interest: None Declared